Bestrophin 1 – Phenotypes and Functional Aspects in Bestrophinopathies. (3rd July 2015) - Pasquay, Caroline; Wang, Lu Fei; Lorenz, Birgit; Preising, Markus N.
Abstract: This is to review the current state of knowledge on the functional and clinical aspects of bestrophin 1, a prominent member of a family of proteins involved in the control and properties of the light peak of the EOG. Initially human bestrophin 1 gene ( BEST1 ) mutations were identified to underlie Best vitelliform macular dystrophy (VMD), a dominantly inherited, juvenile-onset form of macular degeneration. In the recent past the phenotypical spectrum of retinal disorders associated with BEST1 mutations has been extended and the term bestrophinopathies was coined. The physiological role of bestrophin 1 is still not completely understood but has been linked to the generation of a transepithelial chloride current by controlling voltage-dependent calcium channels (VDCC). Dysfunction of bestrophin 1 may result in abnormal ion and fluid transport by the retinal pigment epithelium (RPE) disturbing and even disrupting direct interactions between the RPE and the photoreceptors.